RELATIONSHIP OF TREATMENT-SEEKING BEHAVIOR WITH MAINTENANCE OF STREET CHILD HEALTH IN MAGETAN REGENCY - Nendya Oktavialia (Jurnal EduHealth, 2020)
This study aims to find out the behavior of the search for treatment with the maintenance of street children's health in the maospati region of magetan regency. The behavior of seeking treatment in street children in the maospati region of Magetan regency is in general is often done by self-medicing by buying drugs in stalls when sick. Street children in the maospati region of Magetan district check their health only if they are affected by raids, because some of them almost never check their health regularly. This behavior causes health maintenance that is done less than optimal so that there are still many children who do not know how to maintain their health properly. This type of research is quantitative using a cross sectional approach. The sample in the study was street children in the maospati region of Magetan regency aged an average of 7-16 years, with a sample of 30 respondents and using accidental sampling techniques. Data is processed using methods, univariate, bivariate and chi-square. The search for treatment of street children who do treatment as many as 14 people (46.7%) with good health maintenance as many as 13 people (43.3%). The behavior of street children who did not do treatment as many as 16 people (53.3%) with less health maintenance as many as 17 people (56.7%). The results of the Chi Square Test analysis of treatment search behavior with the maintenance of street children's health in the maospati region of Magetan regency obtained a value of p value = 0.033 with a value of α = 0.05. Thus Ho was rejected which means there is a relationship between Treatment Search Behavior and Maintenance of Street Children's Health in Maospati Region of Magetan Regency.